Perilaku Suap dalam Penyelesaian Tilang oleh Masyarakat Kepada Polisi Lalu Lintas Percut Sei Tuan (Pendekatan Sosiologi Hukum) - Tika Puspita Sari; Agusmidah Agusmidah (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
The community generally bribes traffic police because they want to finish quickly and the assumption is that the Percut Sei Tuan community always thinks that the ticket process is convoluted, difficult and complicated and takes time and effort to make people lazy to complete the ticket in accordance with the proper procedures for solving a ticket, the length of the process law enforcement and long queues become images in the minds of the public when passing through official law enforcement channels. This will no longer be indifferent to the opportunity for the Percut Sei Tuan Police to resolve traffic violations peacefully by accepting bribes from the public. This research is a type of descriptive research. The data in this study is primary data or data collected by the researchers themselves. Data collection techniques in this study are interviews, questionnaires, and observation as well as literature. The data obtained were analyzed using the Miles and Huberman qualitative data analysis technique. The results of the study show that the motives that cause people to bribe in completing fines to the Percut Sei Tuan Police are internal factors: traffic violations are considered normal, public awareness is low, people want to be practical, people are lazy through official procedures following ticket trials or paying fines to banks is difficult and requires a long process. External factors: economy, sense of kinship. While efforts to deal with bribery: Police who abuse their authority by accepting bribes by the public in completing ticketing without going through a set procedure will be subject to sanctions by the National Police's professional code of ethics, imposing criminal fines for traffic offenders, the need for outreach to the public.